The fantastic in modern Japanese literature : the subversion of modernity - Napier, Susan Jolliffe, 1955- (Nissan Institute/Routledge Japanese studies series, 1996)
Modern Japan's repressed anxieties, fears and hopes come to the surface in the fantastic. A close analysis of fantasy fiction, film and comics reveals the ambivalence felt by many Japanese towards the success story of the nation in the twentieth century. The Fantastic in Modern Japanese Literature explores the dark side to Japanese literature and Japanese society. It takes in the nightmarish future depicted in the animated film masterpiece, Akira, and the pastoral dream worlds created by Japan's Nobel Prize winning author Oe Kenzaburo. A wide range of fantasists, many discussed here in English for the first time, form the basis for a ground-breaking analysis of utopias, dystopias, the disturbing relationship between women, sexuality and modernity, and the role of the alien in the fantastic.